Development of an Introduction to Basic Mathematics Textbook Integrated with Islamic Values - Nursupiamin Nursupiamin; Rafiq Badjeber; Bagus Bagus (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2023)
Abstract:Mathematics can be used as an approach to explaining several Islamic by interconnecting using conceptual and meta-mathematical foundations, thus producing integrated mathematics teaching materials. This study aims to describe the development of an integrated Introduction to Basic Mathematics textbook with Islamic values and then see student responses to the textbook. The type of research used is Research and Development (R&D) which refers to modified 4-D models. The instruments used are product validation sheets and response questionnaires. The data obtained were analyzed quantitatively and qualitatively. The results showed that the textbook Introduction to Basic Mathematics integrated with Islamic values was valid by the validators and very suitable for use by students with interesting categories. This finding can be the basis for the development of teaching materials by integrating Islamic values in Islamic universities.Abstrak:Matematika dapat digunakan sebagai pendekatan dalam menjelaskan beberapa ajaran Islam dengan cara interkoneksi menggunakan dasar konseptual maupun meta-matematis, sehingga menghasilkan bahan ajar matematika yang terintegrasi. Penelitian ini bertujuan mendeskripsikan pengembangan buku ajar Pengantar Dasar Matematika terintegrasi nilai keislaman kemudian melihat respon mahasiswa terhadap buku ajar tersebut. Jenis penelitian yang digunakan adalah Research and Development (R&D) yang mengacu pada model 4-D yang dimodifikasi. Instrumen yang digunakan adalah lembar validasi produk dan angket respon. Data yang diperoleh, dianalisis secara kuantitatif dan kualitatif. Hasil penelitian menunjukkan buku ajar Pengantar Dasar Matematika yang terintegrasi nilai-nilai keislaman dinyatakan valid oleh tim validator dan sangat layak digunakan oleh mahasiswa dengan kategori menarik. Temuan ini dapat menjadi dasar pengembangan bahan ajar dengan mengintegrasikan nilai-nilai keislaman di perguruan tinggi keislaman.